Phytosociological analysis of montane-subalpine dwarf willow shrub communites in the Julian Alps and on the Trnovski gozd plateau (NW and W Slovenia) - Dakskobler, Igor; Surina, Boštjan (Hacquetia, 2018)
By means of a phytosociological analysis of 72 relevés of montane-subalpine shrub communities with dominating Rhododendron hirsutum, Salix waldsteiniana, S. glabra and S. appendiculata from the Julian Alps and the the Trnovski Gozd Plateau and by comparing them with similar communities elsewhere in the Alps and the Dinaric Alps we described a new association Laserpitio peucedanoidis-Salicetum waldsteinianae, a new subassociation Rhododendretum hirsuti vaccinietosum myrtilli, two new subassociations of the association Dryado-Rhodothamnetum chamaecisti that had recently been described in the Dolomites (-caricetosum frmae, -salicetosum waldsteinianae), as well as a new association Heliospermo pusillae-Rhododendretum hirsuti. We classifed the glabrous willow community in the study area into a new association Homogyno sylvestrisSalicetum glabrae and proposed a new name – Rhododendro hirsuti-Salicetum appendiculatae for the large-leaved willow community, which we subdivided into two geographical variants: var. geogr. Paederota lutea (Julian Alps, Trnovski Gozd Plateau) and var. geogr. Hypericum grisebachii (Liburnian Karst).